The Study of Self-Relation on the Level of the Person’s Self-Consciousness - Sargsyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
One of the main fundamental problems of modern psychology is the research of the self-relation phenomenon. This particular problem was clarified in the field of psychology and that phenomenon got a name “self-relation” after the years of 1970’s, that before in the various trends of the psychological science was studied o nthe level of person’s self-consciousness, being equalized with the conceptions of “I”, “self-equalization”, “self-appraisal” and “I - concept”. Therefore, for the correct formation of the understanding about self-relation we consider it necessary its further study on the level of the person’s self-consciousness.